A CASE OF SECONDARY MEMBRANOUS NEPHROPATHY DUE TO TUBERCULOSIS - Gan, Yi Lung; Al-Dujaili, Murad; Bavakunji, Riaz (Journal of Ayub Medical College Abbottabad, 2024)
Membranous nephropathy is a common cause of proteinuria and nephrotic syndrome all over the world. It is classified as primary and secondary membranous nephropathy where primary disease formed around 70% of all the cases while the remaining cases could be secondary to autoimmune disease like systemic lupus erythematosus, rheumatoid arthritis, sarcoidosis and Sjogren’s syndrome or solid organs tumors or drugs like NSAIDs and penicillamines and as our case today could be secondary to infective etiologies such as Tuberculosis, Hepatitis B, C, HIV and Syphilis. In this writeup we present a rare cause of secondary membranous nephropathy due to tuberculosis.